Detention Pending Execution of the European Arrest Warrant – Dutch and Polish Experience. Some Reflection from the Human Rights Perspective - Glerum, Vincent; Wąsek-Wiaderek, Małgorzata (Review of European and Comparative Law, 2023)
This article focuses on detention pending surrender, i.e. detention of the requested person in the executing Member State on the basis of the European Arrest Warrant (EAW). It defines the scope of application of Article 5 of the European Convention on Human Rights to such detention and analyses the case-law of the Court of Justice of the European Union on time limits of keeping the requested person in detention in the executing MS as well as on the notion of “the executing judicial authority” entitled to decide on detention pending surrender. Both issues are explored with reference to national law and practice of the Netherlands and Poland. The article provides the answer to the question whether national provisions which limit the duration of detention pending surrender properly reflect the normative content of the framework decision on the EAW. The answer to this question is given with due regard to the standard of protection of the requested person stemming from Article 5 § 1 ECHR and Article 6 of the Charter of Fundamental Rights. Furthermore, the analyses focus on Dutch and Polish provisions concerning the authority entitled to decide on detention pending surrender and their compliance with the CJEU’s jurisprudence on the notion of “the executing judicial authority.” Recognising that detention is the basic measure for ensuring the effectiveness of surrender, we try to define the limits of its use in the EAW procedure, stemming from the requirements of protection of human rights.